E-pharmacophore screening and induced fit docking of phytocompounds against human dihydroorotate dehydrogenase - PRIYA SWAMINATHAN (International Journal of Pharma and Bio Sciences, 2017)
Human Dihydroorotate dehydrogenase (DHODH) is the fourth enzyme in the de novo pyrimidine biosynthetic pathway. Leflunomide is rapidly metabolized to its active form, A77 1726. Two mechanisms of action have been identified for A77 1726: inhibition of dihydroorotate dehydrogenase (DHODH) and inhibition of tyrosine kinases. Leflunomide is a novel drug with proven efficacy in rheumatoid arthritis but it is a synthetic inhibitor for DHODH which can cause side effects in the form of hepatotoxicity. Leflunomide is known to have two properties which from the literature as immunomodulatory and anti-rheumatic drug. Based on this activity of the leflunomide, the natural compounds in the Dr. Duke’s database was searched and 62 compounds which are both, immunomodulatory or anti-rheumatic are collected from PubChem. An already validated E-pharmacophore model for leflunomide was searched against these compounds. The search resulted in three lignin based phytocompounds that was found to be most similar to leflunomide. Further, binding efficiency studies using induced fit docking was performed to explore the possibility that they could be inhibitors of human DHODH. This study helps to shortlist novel compounds from Duke’s database as inhibitors of human DHODH.